STRATEGI PEMANFAATAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN ILMU TAJWID PADA MATA PELAJARANAL-QUR'AN HADITS DI SMK MUHAMMADIYAHDELANGGU KLATEN TAHUN AJARAN 2025/2026 - Ayu Novita Pamujianti; Muhammad Isa Anshory; Viki Bayu Mahendra (STKIP Pesisir Selatan, 2026)
This study was motivated by the importance of utilizing digital technology in Tajwid learning as an effort to improve the effectiveness of material delivery and students’ understanding of tajwid rules. This study aimed to describe the learning process of Tajwid, analyze strategies for utilizing digital technology, and identify supporting and inhibiting factors in Tajwid learning at SMK Muhammadiyah Delanggu. This study employed a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation. The research subjects consisted of six Islamic Religious Education teachers and three students selected through purposive sampling. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, while data validity was tested using source and technique triangulation. The results showed that Tajwid learning at the school still faces various challenges, particularly differences in students’ basic ability to read the Qur’an. The utilization of digital technology was implemented through the use of LCD projectors, laptops, smartphones, PowerPoint, YouTube, WhatsApp, Google Drive, and digital quiz applications.